Guns, germs, and steel the fates of human societies - Diamond, Jared M. (New York W W Norton, 1997)
Why did Eurasians conquer, displace, or decimate Native Americans, Australians, and Africans, instead of the reverse? In this groundbreaking book, evolutionary biologist Jared Diamond stunningly dismantles racially based theories of human history by revealing the environmental factors actually responsible for history's broadest patterns.
Here, at last, is a world history that really is a history of all the world's peoples, a unified narrative of human life even more intriguing and important than accounts of dinosaurs and glaciers. A major advance in our understanding of human societies, Guns, Germs, and Steel chronicles the way that the modern world, and its inequalities, came to be. It is a work rich in dramatic revelations that will fascinate readers even as it challenges conventional wisdom.
Ch. 10. Spacious Skies and Tilted Axes: Why did food production spread at different rates on different continents? -- Ch. 11. Lethal Gift of Livestock: The evolution of germs -- Ch. 12. Blueprints and Borrowed Letters: The evolution of writing -- Ch. 13. Necessity's Mother: The evolution of technology -- Ch. 14. From Egalitarianism to Kleptocracy: The evolution of government and religion -- Ch. 15. Yali's People: The histories of Australia and New Guinea -- Ch. 16. How China became Chinese: The history of East Asia -- Ch. 17. Speedboat to Polynesia: The history of the Austronesian expansion -- Ch. 18. Hemispheres Colliding: The histories of Eurasia and the Americas compared -- Ch. 19. How Africa became Black: The history of Africa -- Epilogue: The Future of Human History as a Science.
Includes bibliographical references and index.
Keywords: Social evolution; Civilization -- History; Ethnology; Human beings -- Effect of environment on; Culture diffusion